2017
DOI: 10.1038/srep45584
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Bandgap Engineering in Monolayer Hexagonal Boron Nitride

Abstract: Monolayer hexagonal boron nitride (h-BN) possesses a wide bandgap of ~6 eV. Trimming down the bandgap is technically attractive, yet poses remarkable challenges in chemistry. One strategy is to topological reform the h-BN’s hexagonal structure, which involves defects or grain boundaries (GBs) engineering in the basal plane. The other way is to invite foreign atoms, such as carbon, to forge bizarre hybrid structures like hetero-junctions or semiconducting h-BNC materials. Here we successfully developed a genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 47 publications
4
57
1
1
Order By: Relevance
“…Our results are consistent with the theoretical results where h‐BN was found to have band gap of 4.47 eV . Experimentally measured band gap of h‐BN is 6.07 eV . The reason that the calculated band gap is less than the experimental value is due the fact that DFT always underestimates the band gap.…”
Section: Resultssupporting
confidence: 91%
“…Our results are consistent with the theoretical results where h‐BN was found to have band gap of 4.47 eV . Experimentally measured band gap of h‐BN is 6.07 eV . The reason that the calculated band gap is less than the experimental value is due the fact that DFT always underestimates the band gap.…”
Section: Resultssupporting
confidence: 91%
“…In the alternative option, it was substituting C atoms to form hybrid lattice of h-BNC in place of h-BN. A general chemical method reported in this context to prepare different h-BN derivatives confirmed that the chemical structure could very well be modified with or without a graphene precursor to tune the BG up to ~2eV [23][24][25].…”
Section: Other Hybrid 2d-monolayersmentioning
confidence: 94%
“…It is quite likely that hybrid structure are constituted with alloys or mixed domains of h-BN, graphene and h-BNC. Especially, when the conversion exceeds 15min, the D peak of graphene starts to slowly blue shift from 1354 cm −1 to the h-BN's E2g peak at 1368 cm −1 [23,26,30,31].…”
Section: Other Hybrid 2d-monolayersmentioning
confidence: 99%
See 2 more Smart Citations